Recent Advances in Understanding the Electron Transport Through Metal-Azurin-Metal Junctions - Romero-Muñiz, C.; Vilhena, J. G.; Pérez, R.; Cuevas, J. C.; Zotti, L. A. (Frontiers in Physics, 2022)
Azurin proteins are the workhorse of protein electronics. This is a branch of biomolecular electronics, a recent research field which investigates electronics based on biomolecules such as proteins, peptides, amino acids, bacterial nanowires or DNA. In general, the possibility of including biosystems in solid-state junctions has opened the way to the development of novel electrical devices, and proteins have attracted enormous attention thanks to their many interesting properties. In the particular case of metal-azurin-metal junctions, experimental measurements have revealed extremely efficient electron transport over large distances, showing conductance values which are higher than certain conjugated molecules of similar lengths. Moreover, the electrical current has often been found to be temperature-independent, which has been used as an evidence of coherent transport or quantum tunneling. Interesting effects have been observed, moreover, upon insertion of single amino-acid mutations. In spite of a huge amount of work, the exact mechanism for the charge flow through these systems is still under debate. In this review, we will revise the recent advances made in the electron-transport measurements of azurin-based junctions as well as the corresponding theoretical modelling. We will discuss the interpretation of the currently-available experimental results as well as the open issues which still remain to be clarified.